Analysis of the Epidemic and Epizootic Situation on Brucellosis around the World in 2019 and the Forecast for the Russian Federation for 2020 - D. G. Ponomarenko; D. V. Rusanova; A. A. Khachaturova; O. N. Skudareva; O. V. Logvinenko; E. I. Rakitina; M. V. Kostyuchenko; O. V. Semenko; O. V. Maletskaya; A. N. Кulichenko (Проблемы особо опасных инфекций, 2020)
The paper presents the data on brucellosis incidence in a number of countries around the world. An assessment of the epizootic and epidemic situation of brucellosis in the Russian Federation in 2019 is performed. In 2019, Russia maintains the presence of an unfavorable epizootic situation for brucellosis. An increase in the number of brucellosis infected cattle by 14 % and primary foci of small cattle infection by 52 % was established. Epizootics of bovine brucellosis were mainly recorded in the North Caucasus (63.5 %), Southern (19.9 %) and Volga federal districts (7.4 %). The main number of points unfavorable for brucellosis of small cattle, and sick sheep and goats were detected in two federal districts – North-Caucasian (36.8 %) and Southern (26.3 %). The epidemic manifestations of brucellosis in the Russian Federation are closely related to the activity of the epizootic process among the main epidemiologically significant species of farm animals. In 2019, Russia registered 397 human brucellosis cases (0.27 0/0000 including 23 (0.08 0/0000 among minors. The number of cases of brucellosis and the value of the incidence rate in 2019 are comparable with long-term average data over the past 10 years. The largest number of human brucellosis cases, as in previous years, was established in the North-Western Federal District (278 cases, 70.4 % of the total number of cases) and the Southern Federal District (59 cases, 14.9 %). There is an increase in the relative long-term incidence of brucellosis in the Republic of Dagestan, Voronezh, Penza Regions and the Republic of Kalmykia. In the territories of these subjects in 2019, atense epizootic situation regarding brucellosis among cattle and small cattle was noted. Taking into account the current epizootic and epidemic situation and the long-term dynamics of brucellosis situation development in the Russian Federation, in 2020 it is possible to predict human brucellosis incidence at the level of 0.23–0.27 0/0000.